The basics of oil spill cleanup - Fingas, Mervin F. (CRC Press/Taylor & Francis, 2012)
"An examination of pollution caused by crude oils and petroleum products derived from them, this book covers how oil spills are measured and detected and discusses the properties of the oil as well as its long-term fate in the environment. This third edition contains a new chapter devoted to pollution effects on wildlife. It focuses on the cleanup of oil spills that occur in water, since these spills spread most rapidly and cause the most visible environmental damage. It also includes coverage of the latest technologies as well as recent spills, including the Gulf of Mexico"-- Provided by publisher.
Keywords: Oil spills -- Cleanup.; Oil pollution of the sea -- Environmental aspects -- North America.; elektronické knihy; electronic books